Importance of nursing consultation during endoscopic pre-examination in outpatient clients - Silva , Yanna Georgia Crispiniano Ferreira da; Silva, Liniker Scolfild Rodrigues da (Seven Editora, 2023)
Upper digestive endoscopy (UDE) is a method of diagnostic examination that consists in the use of flexible fiber optic devices, making it possible to assess alterations in the upper digestive tract, including the esophagus, or stomach, and the initial portion of the duodenum. Thus, the disease is constantly concerned with the improvement of the assistance provided to the patients, always aiming to seek knowledge to systematize and organize their practice and their care process. Considering the attributions of the sick for the endoscopic interventions, this study aims to find out in the literature the importance and the role of the sick consultation in the endoscopy pre-examination of outpatients. This is a literature review study, of the integrative review type, with a timeless delimitation, carried out in the period from January to March 2023. In the execution of the guiding question, the PICo strategy was applied (P: Outpatients; I: Consultation of nursing; Co: Pre-exams of endoscopy). On the other hand, I deliberated on the following question: What is the importance of the nursing consultation for patients in pre-examination of endoscopy at the outpatient level? Then, it was searched in the databases: Medical Literature Analysis and Retrieval System Online, Embase, SCOPUS, Web of Science and the Scientific Electronic Library Online virtual library. 10,047 studies were found, however, at the end of the analysis process, only 6 articles were included in the study. We will observe the need for more in-depth studies on the importance of the consultation of patients without endoscopic pre-examination at the ambulatory level. The understanding of the information present at a certain point in the need for the patient's patient's consultation in the pre-endoscopic examination is essential for the emergence of more comprehensive assistance planning and in its coverage so that this service is offered in such a way that the patient has better comfort and safety in the lent procedure. DOI:https://doi.org/10.56238/sevened2023.006-030